Deep eutectic solvent as a highly efficient reaction media for the one-pot synthesis of benzo-fused seven-membered heterocycles. Issue 33 (17th August 2016) - Shaabani, Ahmad; Hooshmand, Seyyed Emad; Nazeri, Mohammad Taghi; Afshari, Ronak; Ghasemi, Shima
Graphical abstract: Highlights: Use of a deep eutectic solvent for the synthesis of benzo-fused seven-membered heterocycles. Mild reaction conditions with good to excellent yields in short reaction times. Potential applications in synthetic and medicinal chemistry. Abstract: The combination of choline chloride and urea as a deep eutectic solvent has been applied to the synthesis of benzo-fused seven-membered heterocycles, including tricyclic 1, 4-benzodiazepines and 1, 4-benzoxazepines, via a one-pot, three-component reaction. The reaction conditions are relatively mild and do not require additional metals, acid catalysts, or organic solvents. The protocol has the advantages of excellent yields in short reaction times, an easy workup procedure, and being environmentally friendly.